TINJAUAN YURIDIS TERHADAP ANAK BEDA AGAMA BERDASARKAN HUKUM ISLAM - Silviani, Sania (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTWith its diversity of culture, race, customs, and religions, Indonesia is faced with a variety of legal perspective issues, in this case, related to controlling the change of belief and inheritance. These view differences often create legal problems, especially when it comes to inheritance. In Islamic law, it is defined that the right of children with a different religion to claim their parents' assets after they die will be obstructed (hijab). This Islamic inheritance law is different from the Indonesian civil law. Therefore, it is interesting to examine the inheritance law according to Islamic law in Indonesia. This study employs a normative method that analyses data from both primary and secondary legal materials. This study aims to determinehow Islamic law applies to the juridical evaluation of children with different religions. This examination is crucial because children are the descendants and the successors of theirparents. However, at a time when religious differences complicate their inheritance right, it will become a serious issue. In Islamic law, it does not necessarily mean that children will lose their right to a legal review or their inheritance right. It has been explained in The Quran and Shahih Bukhari that children with different religions due to conversion are highly praised. It is also stated that children will inherit their parents' assets through a method of “gift” or giving someone a present while they are still alive.